The Level Of Understanding of Elementary Students In Terms Of Learning Methods And Students’ Learning Motivation - Arifin, Moch. Bahak Udin By; Nurdyansyah, Nurdyansyah; Daud, Normadiah Binti (Madrosatuna: Journal of Islamic Elementary School, 2025)
This study determined and analyzed the effect of learning methods and motivation to learn students on students’ level of understanding at Hidayatul Mubtadi’en elementary school students, Kedungwaru, Tulungagung. The type of research used quantitative method with data collection technique used questionnaire and documentation. Data analysis techniques using simple correlation tests and multiple regression tests. The population of this study was Hidayatul Mubtadi’ en Elementary School students. The result of this study shows: 1) there is an influence between learning methods to students’ level of understanding. So using the correct learning methods can increase the student’s level of understanding. 2) there is an influence between motivation to learn and students’ understanding level. So teachers as parents at school can give the spirit and motivation to learn that makes the students active in learning and know the direction of learning so that it can reach the optimal learning outcomes. 3) there is an influence between learning methods and motivation to learn to students’ level of understanding. So that can be concluded learning methods and motivation to learn to have an important role in students’ level of understanding in the learning process.